HIV‐1 Tat Peptide‐Gemcitabine Gold (III)‐PEGylated Complex—Nanoflowers: A Sleek Thermosensitive Hybrid Nanocarrier as Prospective Anticancer. (7th June 2018) - Liu, Hui; Jiang, Peng; Li, Zhonghu; Li, Xiaowu; Djaker, Nadia; Spadavecchia, Jolanda
Abstract: This paper focuses on the synthesis of novel metal‐drugs nanoparticles based onto gold‐gemcitabine complexes relevant for biomedical applications. Gold (HAuCl4 ) is mixed with antitumor compounds (gemcitabine (GEM)) and dicarboxylic acid–terminated polyethylene‐glycol (PEG), which plays a double role as surfactants and reducing agent. The proposed methodology is fast and reproducible and leads the formation of hybrid‐metal nanoflowers called GEM ION‐PEG‐AuNPs, in which drug solubility and efficiency are improved. The emerging role of GEM ION PEG‐AuNPs in the hyperthermic treatment was applied in pancreatic cancer cells under specific experimental conditions. For this purpose GEM ION‐PEG‐AuNPs are decorated with HIV‐1 Tat peptide, a potent trans ‐activator of transcription from the viral promoter and is essential for viral replication containing an activation domain and a nucleic acid‐binding domain. All products are evaluated by various spectroscopic techniques (Raman and UV–vis) and transmission electron microscopy (TEM). This study, revealing an original chemical approach, will employ an important position in the field of nanomedicine, with novel perspectives that will be proposed for the development of new drugs and active targeting in cancer therapy. Abstract : Design and synthesis of HIV‐1 Tat GEM ION‐PEG‐AuNPs by pegylated method and ability of internalization in pancreatic adenocarcinoma cancer cells (PANC‐1) for phototherapy applications.